Efektivitas Pelayanan Aparat Kampung dalam Meningkatkan Pelayanan Publik di Kampung Yanggandur Kabupaten Merauke - Hubertus; Tambajong, Hesty (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2025)
Yanggandur Village, Sota District, Merauke Regency has the task of providing services to all elements of society regardless of social status in order to provide excellent service to the community.The purpose of this study is to determine the Effectiveness of Village Officials in Improving Services in Yanggandur Village, Sota District, Merauke Regency. This study uses a qualitative research method with a descriptive approach. The data collection technique uses observation, interview, and documentation techniques. The results of this study illustrate that the effectiveness of the work of village officials in improving services in Yanggandur Village, Sota District, Merauke Regency in the implementation of services has not been carried out effectively. This happens because there is still a lack of government responsibility, especially village officials in providing good services to the community. The initiative of the village officials to adapt to the community environment and also the lack of village office facilities so that all activities do not run well and efficiently. For the Yanggandur village apparatus in order to improve the quality of service, meet the needs of the community well and also build relationships with a more participatory approach with the community so that the services provided will produce good results.